An investigation of self-medication and its correlates among community dwelling elderly population by applying health belief model - Sara Esmaelzadeh Saeieh; Leili Salehi*; Raziyeh Esmaelpour (Tehran University of Medical Sciences, 2018)
Background & Aim: Self- medication is defined as consuming nonprescription medicines to treat self-diagnosed disorders or symptoms. This study was carried out to examine prevalence of self-medication during three months ago and its correlates among the elderly population in Karaj-Iran by using the HBM model. Materials & Methods: This cross sectional study was conducted on 189 elderlies who were covered by health care centers. The inclusion criteria were absent of cognitive disorders and being over the age of 60. The multistage sampling was used in this study. The data collection tools included: demographic characteristics and a questionnaire based on the HBM model, including knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers. Statistical analysis of the data was performed using chi-square tests, Student t-tests, ANOVAs and multiple logistic regressions. Analyses were done by SPSS 19.0. Results: The prevalence of self-medication was 26.5%. The most common medicine used for self-medication was Supplements (87.30%), cold drugs (40.2%), and pain killers (39.6). There was significant correlation between self-medication and health insurance coverage (P=0.01) and chronic diseases (P=0.001).There were two predictors of self -medication behavior in our study, which were having chronic disease and perceived susceptibility with OR were 1.46(95% CI:0.71-2.40) and 0.93(95%CI:0.76-1.13), respectively. Conclusion: Due to the study results, it is suggested that an interventional program should be considered the promoting of the perceived susceptibility of the elderly population regarding self-medication and policy makers should be noted to elderly health insurance coverage.